The Relationship Of External Factors To Student Achievement Level Iii Study Program Diii Midwifery Karawang Poltekkes Kemenkes Bandung - Eka Kartika (International Journal of Health Engineering and Technology, 2022)
Advances in science, technology and the demands of society are increasingly critical of midwifery services provided by midwives give consequences to graduates of midwife education to improve hard skills, soft skills and knowledge and act according to their competence and authority. In DIII Midwifery Karawang Poltekkes Bandung Ministry of Health obtained data that third level students who have a cumulative achievement index above 2.75 as much as 25.68% and students who have a cumulative achievement index below 2.75 that is as much as 73.52%. The general purpose of this study is to determine the relationship of external factors to student achievement level III study program DIII Midwifery Karawang Poltekkes Kemenkes Bandung. The research was conducted descriptively with total population, cross sectional approach. The population of this study is all midwifery students Level III semester V Prodi DIII Midwifery Karawang Poltekkes Kemenkes Bandung. This research sample was taken in total as many as 68 students. After a statistical test, it was stated that there is a meaningful relationship between the physical environment of the campus (p=0.034) with student achievement, while the support of parents (P=0.716) there is no meaningful relationship with student achievement III level of Midwifery Study Program in Karawang Poltekkes Kemenkes Bandung.